Amatoxin and phallotoxin concentration in Amanita phalloides spores and tissues. (December 2015) - Kaya, Ertugrul; Karahan, Selim; Bayram, Recep; Yaykasli, Kursat Oguz; Colakoglu, Serdar; Saritas, Ayhan
Most of the fatal cases of mushroom poisoning are caused by Amanita phalloides . The amount of toxin in mushroom varies according to climate and environmental conditions. The aim of this study is to measure α -, β -, and γ -amanitin with phalloidin and phallacidin toxin concentrations. Six pieces of A. phalloides mushrooms were gathered from a wooded area of Düzce, Turkey, on November 23, 2011. The mushrooms were broken into pieces as spores, mycelium, pileus, gills, stipe, and volva. α -, β -, and γ -Amanitin with phalloidin and phallacidin were analyzed using reversed-phase high-performance liquid chromatography. As a mobile phase, 50 mM ammonium acetate + acetonitrile (90 + 10, v/v) was used with a flow rate of 1 mL/min. C18 reverse phase column (150 × 4.6 mm; 5 µm particle) was used. The least amount of γ -amanitin toxins was found at the mycelium. The other toxins found to be in the least amount turned out to be the ones at the spores. The maximum amounts of amatoxins and phallotoxin were found at gills and pileus, respectively. In this study, the amount of toxin in the spores of A. phalloides was published for the first time, and this study is pioneering to deal with the amount of toxin in mushrooms grown in Turkey.